Analisis Peramalan Penjualan Bapau Hijau Pada Skala Usaha Rumah Tangga Ibu Tata - Lupita Cesar Dian Pradigmawati; Suhono Suhono (Jurnal Ilmiah Wahana Pendidikan, 2023)
Forecasting is a method for estimating a value in the future using past data. This research was conducted on the scale of Mrs. Tata's household business. Mrs. Tata produces green bapau every day which will be distributed to three places, namely stores A, B and C. Sales at these three places fluctuate every day, as a result it is not uncommon for many products to be unsold, resulting in losses. In addition, it also resulted in the procurement of production raw materials that were not in accordance with the sales results. So far, Mrs. Tata, in procuring raw materials, is not dynamic every day or is not adjusted to the next day's sales forecast because she has not used a prediction system. Therefore it is necessary to have a system that can predict sales every day. The prediction system is made using the least squares method. The data used is sales data from November 1 2022 to December 31 2022. The predicted period is the next fifty nine days. From the calculation results, it can be concluded that the green bapau sales prediction system can predict sales in the next period. The least square method can be used to predict green bapuu sales by forecasting sales at stores A, B and C for the next 59 days, namely 1,253 pcs, 1,217 pcs and 1,276 pcs.